1987
DOI: 10.1002/1097-0142(19870801)60:3+<692::aid-cncr2820601541>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and epidemiologic data on urologic cancer

Abstract: HIS ARTICLE provides statistical and epidemiologic T information on cancer of the urogenital organs.Data on incidence, probability, mortality, treatment, and survival are presented for cancer of the prostate and other male genital cancers, kidney, and bladder. Some of the leading epidemiologic aspects in the research of each of these cancers are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
10

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 78 publications
(13 reference statements)
0
9
1
10
Order By: Relevance
“…In contrast to other reports [8][9][10] that had shown that low grade superficial tumors comprised 80% of all TCC of the bladder, our study revealed that only 35.7% of TCC in the Riyadh area were superficial, while approximately 65% had evidence of muscle invasion at the time of initial presentation. Friedel et al 11 suggested that all bladder cancers progress through a sequence of events in which initially superficial tumors, if left untreated, become invasive and infiltrate the lamina propria, the muscularis mucosa and finally penetrate the perivesical fat.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to other reports [8][9][10] that had shown that low grade superficial tumors comprised 80% of all TCC of the bladder, our study revealed that only 35.7% of TCC in the Riyadh area were superficial, while approximately 65% had evidence of muscle invasion at the time of initial presentation. Friedel et al 11 suggested that all bladder cancers progress through a sequence of events in which initially superficial tumors, if left untreated, become invasive and infiltrate the lamina propria, the muscularis mucosa and finally penetrate the perivesical fat.…”
Section: Discussioncontrasting
confidence: 99%
“…7 Since the 1950s, the incidence of bladder cancer in Western countries, including Spain, has increased by 50%. 8 Smoking constitutes the major risk factor for bladder cancer, although PAH exposure is also a risk factor. [9][10][11][12] Polycyclic aromatic hydrocarbons exposure occurs through many occupations or mixtures [such as diesel-engine (classified as group 1) or gasoline-engine (classified into group 2B)], as evaluated by IARC.…”
Section: Introductionmentioning
confidence: 99%
“…A ocorrência de mutações no epitélio vulvar, no decorrer do processo de envelhecimento, é a melhor explicação para o aumento significativo da incidência de cân-cer vulvar após os 75 anos de idade (14,41,67). Um método para determinação de clonalidade, baseado na inativação (metilação) do gene receptor de androgênio, situado no cromossomo X, foi desenvolvido recentemente para caracterizar este epitélio (3,76).…”
Section: Estudos De Clonalidade De Lesões Precursoras Hpv Positivas Eunclassified